Hemobilia secondary to choledochal cyst - M.S. Machoki; S.R. Hussain; Laving A; Okiro P; Muthee B (Elsevier, 2021)
Non variceal upper gastrointestinal hemorrhage in children is rare. A 5-year-old presented with hematemesis and melena. Pre-referral imaging and exploratory laparotomy did not reveal the source of bleeding. Hemobilia was detected on endoscopy MRI showed a choledochal cyst. The patient underwent successful resection of the cyst and hepaticojejunostomy.